Synergistic effects of boron and cadmium on the metal enrichment and cell wall immobilization capacity of Cosmosbipinnatus - Yu, Xiaofang (Plant physiology and biochemistry : PPB, 2024)
Copyright © 2024 Elsevier Masson SAS. All rights reserved.